MANAGING CLASSROOM: TEACHERS' STRATEGIES AND CHALLENGES (PIONIR: JURNAL PENDIDIKAN, 2024)
Classroom management ensures optimal teaching and learning processes, especially in thematic learning. Teachers often face challenges requiring specific coping strategies, particularly because students are still young. This study describes the strategies and challenges teachers face in classroom management during thematic learning at an Islamic Elementary School in Banda Aceh. The researchers used observation sheets and interview lists to guide this qualitative research. The findings revealed that the classroom management strategies employed by second-grade teachers at the school include weekly reorganization of student seating arrangements, engaging students through question-and-answer sessions and games, classroom administration by designing lesson plans (RPP), taking attendance, providing a reading corner, ensuring availability of trash bins, keeping student personality notes, and implementing rewards and punishments. The challenges teachers face in managing the classroom during thematic learning include internal factors such as student motivation and psychological conditions and external factors such as the teacher's proficiency in designing lesson plans that integrate available learning media and facilities.Keywords: Strategy,  Challenge, Classroom management, Thematic learning
Keywords: strategy; classroom management; thematic learning